The significance of Corporate and Regulatory Affairs (CoRA) Department in Banglalink Digital Communications Ltd. - Sharif, Nusrat (BRAC Univeristy, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.